2017
DOI: 10.1159/000466707
|View full text |Cite
|
Sign up to set email alerts
|

Fistula and Survival Outcomes after Fistula Creation among Predialysis Chronic Kidney Disease Stage 5 Patients

Abstract: Background: Most guidelines recommend the creation of arteriovenous fistula (AVF) in patients with chronic kidney disease (CKD) stage 4. However, an increasing number of studies suggest that early AVF creation leads to high rates of AVF failure and death before dialysis commencement. Only the Japanese guideline recommends AVF creation at CKD stage 5; however, no data are available regarding access-related outcomes at this stage. Method: This was a multicenter cohort study involving Japanese CKD stage 5 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
2
2
1
Order By: Relevance
“…The median eGFR at the time of AVF creation was 8.1 mL/min/ 1.73 m 2 in this cohort below the recommended window. Our observations were consistent with previous studies from Canada, Japan, and Australia which reported that incident fistula creations were performed between an eGFR of 7 and 14 mL/min per 1.73 m 2 [5,9,13,14]. This disparity may be attributable to several barriers: delay in referral from a nephrologist, lack of patient education, restricted local resources, and reimbursement policies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The median eGFR at the time of AVF creation was 8.1 mL/min/ 1.73 m 2 in this cohort below the recommended window. Our observations were consistent with previous studies from Canada, Japan, and Australia which reported that incident fistula creations were performed between an eGFR of 7 and 14 mL/min per 1.73 m 2 [5,9,13,14]. This disparity may be attributable to several barriers: delay in referral from a nephrologist, lack of patient education, restricted local resources, and reimbursement policies.…”
Section: Discussionsupporting
confidence: 89%
“…The present study analyzed the clinical outcomes of the patients undergoing predialysis vascular access creation and explored the effects of clinical characteristics at surgery on the likelihood of initiating dialysis during follow-up. We found the majority of patients have predialysis AVF created later than recommended by national guidelines, and a large proportion of patients (91.7%) started hemodialysis within 1 year after AVF surgery, similar to that in a Japanese study [9]. Of the patients who started hemodialysis within 1 year, only 66.5% used AVF on their first hemodialysis session.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although whether the reported survival benefits of arteriovenous access preparation are caused directly by reduced catheter-related infections should be investigated in further studies, a recent study reported that mortality after sepsis was higher in the AVG group than the AVF group [21]. A potential harm of preparing an arteriovenous access is unnecessary creation, defined as an AVF failure or patient death during the predialysis period, and that risk is elevated in elderly patients and female patients [22].…”
Section: ■ Recommended Considerations 1) Benefits and Harmsmentioning
confidence: 99%